Inhibitory effect of THPGV-0 on the histamine release from antigen-induced RBL-2H3 cells - Agung Endro Nugroho; Ritmaleni Ritmaleni; Novrizal Abdi Sahid; Kazutaka Maeyama (Indonesian Journal of Pharmacy, 2010)
Tetrahydropentagamavunon-0  (THPGV-0)  is  assumed  to  be  main metabolite  product  of  biotransformation  process  of  PGV-0.  THPGV-0  was synthesized  by  converting  PGV-0  to  the  compound  by  hydrogenation  with  Pd/C as a catalyst. PGV-0 potently inhibited the histamine release from  rat mast cells in  vitro  and  in  vivo,  however,  ironically  only  traces  amount  of  compound  was found in the blood. THPGV-0 is assumed to have important roles in the biological effects of PGV-0 in vivo. In present study, we investigated the antiallergy effect of  THPGV-0  in  compare  to  this  of  PGV-0  in  vitro.  The  study  was  performed  by using  rat  basophilic  leukemia  (RBL-2H3)  cell  line,  a  tumor  analog  of  mucosal mast  cells.  DNP-BSA,  an  antigen,  was  used  as  an  inducer  for  stimulating  the histamine  release  from  mast  cells.  In  present  study,  THPGV-0  at  low concentration  did  not  succeed  to  inhibit  the  histamine  release,  but  at  higher concentration (30 and 100  M) showed strong effects. THPGV-0 at concentration of  100  M  depleted  the  histamine  release  by  96.10  0.51%.  In  compare  to PGV-0,  THPGV-0  has  higher  efficacy  but  less  potent.  In  the  study,  the possibilities  of  the  spontaneous  release  from  RBL-2H3  cells  by  the  compounds were also observed. All concentrations of THPGV-0 as well as PGV-0 showed low spontaneous histamine release, less than 10 % of the total histamine contained in RBL-2H3 cells.Key words: tetrahydropentagamavunon-0, allergy, histamine, RBL-2H3 cells